2014
DOI: 10.1371/journal.pone.0100844
|View full text |Cite
|
Sign up to set email alerts
|

An Attenuated Herpes Simplex Virus Type 1 (HSV1) Encoding the HIV-1 Tat Protein Protects Mice from a Deadly Mucosal HSV1 Challenge

Abstract: Herpes simplex virus types 1 and 2 (HSV1 and HSV2) are common infectious agents in both industrialized and developing countries. They cause recurrent asymptomatic and/or symptomatic infections, and life-threatening diseases and death in newborns and immunocompromised patients. Current treatment for HSV relies on antiviral medications, which can halt the symptomatic diseases but cannot prevent the shedding that occurs in asymptomatic patients or, consequently, the spread of the viruses. Therefore, prevention ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 100 publications
2
23
0
Order By: Relevance
“…In addition, Tat increased the expansion and differentiation of naïve CD4 þ T cells activated in NPC. These findings, together with the observations made in CD8 þ T cells [15,16,28], confirm that Tat plays an important role in the hyperactivation of the T-cell compartment, a phenomenon characterizing the progression to AIDS and possibly the residual disease observed in successfully ART-treated individuals [29,30].…”
Section: Discussionsupporting
confidence: 70%
“…In addition, Tat increased the expansion and differentiation of naïve CD4 þ T cells activated in NPC. These findings, together with the observations made in CD8 þ T cells [15,16,28], confirm that Tat plays an important role in the hyperactivation of the T-cell compartment, a phenomenon characterizing the progression to AIDS and possibly the residual disease observed in successfully ART-treated individuals [29,30].…”
Section: Discussionsupporting
confidence: 70%
“…To further support our hypothesis, Gavioli et al demonstrated previously that including Tat in a multi-antigenic vaccine enhanced the magnitude and broadened Gag- and Env-specific T cell responses without affecting the quality of the Th2 responses27. Furthermore, the inclusion of Tat in a candidate vaccine against Herpes Simplex Virus type 1 (HSV-1) enhanced the induction of broad, high magnitude effector memory HSV-1 specific CD 8 T cell responses49 that completely protected mice after a lethal intravaginal challenge with wild type HSV-14950 HSV-1. Collectively, this evidence supports the inclusion of Tat as a component of a multi antigenic vaccine and implies that the rHRV-DNA vaccination regimen reported here, that contains Tat and Gag as immunogens, will most likely be highly immunogenic.…”
Section: Discussionmentioning
confidence: 96%
“…at 37 • C [33]. The optical density at 620 nm was determined with "Sunrise optical reader" (Tecan) and then analyzed as previously described [34,35]. For each type-specific VLP, the cut-off values were determined by analyzing the plasma of 24 unvaccinated healthy donors at 1:100 dilution as the mean OD (±3 SD): 0.374 for HPV-16; 0.346 for HPV-18; 0.388 for HPV-6; and, 0.346 for HPV-11.…”
Section: Determination Of Igg Titers and Aviditymentioning
confidence: 99%